Sunday

December 21, 2014

December 21, 2014

Posted by **forest** on Tuesday, May 8, 2007 at 12:40pm.

Change 6y = 9 - 3x to:

3x = -6y + 9, then solve for x by dividing both sides by 3 to get:

x = -2y + 3

when you divided both sides by 3. there is a rule where you cant divide the answer if theirs an addition sign.

so

3x=-6y+9

x=(-6y+9)all over 3

you cant simplify it more than that

**Answer this Question**

**Related Questions**

maths - how do i Rearrange the formula Y = 5X + 7 so that X is the subject. and ...

science - rearrange this equation 2 make x the subect. 6y = 9 - 3x so first i ...

algebra - 7/11 - 2x < 3/10; {1/2, 1/3, 1/4, 1/5, 1/6} Rearrange the ...

algebra - how do I do this Solve for x. 3x – 2y = 6 Add 2y to both sides and ...

Math[Please Help] - Solve the inequality x > 6x - 10 and write a description ...

maths - Solve 1.-6b+1+4b= -3b+6 2.8x - 4x = -8 3.the sum of twice a number and ...

maths - i have to make y the subject of this equation: 4t + 7y - 9 = 0 wod it be...

Math2(Please help) - Directions:Solve and explain the inequality using words....

Precalc - I have a couple questions, I need to know how to solve these type of ...

maths - how do i solve the following equation? 4 - x = 2 - (3 - 2x) remove ( ) ...